Acute Delirium Associated With Levofloxacin - Kogan, Yana (J Clin Med Res, 2018)
Delirium is considered as the most common complication afflicting hospitalized elderly patients, accompanied by high morbidity and mortality rate; and despite its high prevalence, it often remains unrecognized. Drug-induced delirium is a well-known entity with sedatives, narcotics and anticholinergics most often implicated in its causation. Delirium attributed to antibiotics, mainly cephalosporins and macrolids, has been infrequently reported, and until yet only seven cases of levofloxacin-induced delirium have been described in the medical literature. We describe another case of delirium associated with levofloxacin in an elderly patient who was hospitalized in our medical ward for pneumonia. The present case and the other cases previously reported should raise the awareness of physicians to this serious, underestimated, and underdiagnosed adverse effect of a commonly used antibiotic, levofloxacin.